COVID-19 and immunomodulation treatment for women with reproductive failures - Sedláčková, Lenka (Casopis lekaru ceskych, 2021)
COVID-19 pandemic is affecting various areas of health care, including reproductive medicine. Many women with infertility are treated by immunomodulation and immunosuppression in periimplantation period due to underlying autoimmune diseases or cellular immune dysfunction. Many questions have been raised in relation to COVID-19, including susceptibility to SARS-CoV-2 infection in women with immunotherapy, how to manage women with an increased risk of and active COVID-19 infection. International team of reproductive immunologists led by professor Joanne Kwak-Kim prepared a review of information and recommendations for using immunotherapy in women with reproductive disorder in COVID-19 pandemic. Everyday practice need led us to presentation of the synopsis of these interim guidelines for particular treatment modalities.
Keywords: immunotherapy; Infertility, Female; ženské pohlaví; COVID-19; Pandemics; immunotherapy; imunomodulace; Humans; pregnancy; pandemie; Female; reproductive failure; ženská infertilita; lidé; SARS-CoV-2; Immunomodulation